Hybrid learning during the COVID-19 pandemic of engineering students at KMITL, Thailand - Boonchana Purahong; Saran Sithiyopasakul; Paisan Sithiyopasakul; Thanavit Anuwongpinit; Tuanjai Archevapanich; Pattarachai Vichaiva (My University, 2021)
This article presents the hybrid learning model during the COVID-19 for students of Agro-Industrial Systems Engineering who enrolled in the course embedded system, course code 01386304, Faculty of Engineering, King Mongkut's Institute of Technology Ladkrabang for 29 students by selecting a specific sample group. The researcher presented a hybrid learning model during the COVID-19, where students were orientated for the same understanding and followed by teaching as active learning formed project-based learning. Finally, we assessed five aspects of hybrid learning satisfaction during the COVID-19. The evaluation results revealed that the students' satisfaction was at a good level and their arithmetic mean was 4.206 and the standard deviation is equal to 0.74 (X = 4.206, S.D. = 0.74)
Keywords: Technology-Enhanced Education Studies; Online Learning and Analytics; Innovative Teaching Methods